Comparison of Flow Cytometric and Alamar Blue Tests with the Proportional Method for Testing Susceptibility of Mycobacterium tuberculosis to Rifampin and Isoniazid - Reis, Roberto S. (American Society for Microbiology, 2004)
The performance of flow cytometry and the microplate Alamar Blue assay in determining susceptibility of Mycobacterium tuberculosis was assessed by testing 150 Brazilian isolates. The overall agreement was 97.3 and 98% for isoniazid and 94.7 and 100% for rifampin by flow cytometry and MABA, respectively. This study was entirely done in a developing country.